2023
DOI: 10.1055/a-1957-5383
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Reproducibility of Analyzing 3D Transperineal Ultrasound Volumes Obtained in the First Phase of Labor - A Pilot Study

Abstract: Purpose The aim of this study was to investigate the reliability and reproducibility of transperineal ultrasound (TPUS) in the initial phase of labor. As TPUS is a common method, it could supplement vaginal palpation and even replace it in certain situations. In addition, we used a 4-dimensional method for the assessment of cervical effacement. Materials and Methods 54 women in labor were included and underwent TPUS. The resulting images from the acquired 4D volumes were evaluated after the examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…However, it cannot be concluded that TPU measurements were more imprecise, as the actual length of the cervix is unknown. CL measured by TPU has been shown to be reproducible [10] and to be in good agreement with transvaginal measurements of CL [32]. Therefore, we conclude that despite poor agreement in our study, CL measured by TPU could still be valuable in labour management.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…However, it cannot be concluded that TPU measurements were more imprecise, as the actual length of the cervix is unknown. CL measured by TPU has been shown to be reproducible [10] and to be in good agreement with transvaginal measurements of CL [32]. Therefore, we conclude that despite poor agreement in our study, CL measured by TPU could still be valuable in labour management.…”
Section: Discussionsupporting
confidence: 67%
“…However, there is increasing evidence that other examination methods to monitor labour progress may be useful and helpful. TPU has shown to be reproducible [10], significantly less painful than DE and to lessen anxiety levels during the latent stage of labour [12]. Higher anxiety levels have been shown to be associated with a longer time to delivery [38] and higher degrees of pain [39].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation